Topical bromelain cream did not increase neovascularization, fibroblast and epithelialization in wound healing of diabetic-rats (rattus norvegicus) - Maulidha Suzi Annisa; Wimpie Pangkahila; IGM Aman (IJAAM (Indonesian Journal of Anti-Aging Medicine), 2020)
Introduction: The diabetic-wound healing process is longer due to blood vessel ischemia. Bromelain is the enzyme that acts as debridement agent with anti-inflammatory effect. The aim of this study was to prove the topical administration of bromelain increase neovascularization, fibroblast, and epithelialization in wound healing of diabetic-rats. Methods: This study used post-test only control group design. Subjects were 32 male Wistar diabetic-rats (Rattus norvegicus. It was divided into 2 groups (n = 16) and given amoxiciline for 3 days. The control group consist of: O1 group treated with a base cream for 5 days and O2 group was treated for 12 days. While the treatment group consist of: O3 group was treated with 70% bromelain cream for 5 days and O4 group was treated for 12 days. The neovascularization, fibroblasts, and epithelialization were examined histopathologically. Results: The mean number of fibroblasts in O1 and O3 were 222.88±37.94 cells/field of view and 25.38±7.94 cells/field of view, while O2 and O4 were 99.63±82.33 cells/field of view and 32.25±12.453 cells/field of view (p <0.001). The mean number of neovascularization in O1 and O3 were 15.13±1.95 and 2.88±1.80 cells/field of view, while O2 and O4 were 5.50±3.78 cells/field of view and 1.50±1.06 cells/field of view (p <0.001). The epithelial gap size in the O1 and O2 group were 377.56±573.88 μm and 229.04±647.83 μm (p <0,001). Both O3 and O4 groups showed no longer a wound gap (p>0,05). Conclusion: Topical bromelain cream 70% did not increase neovascularization, fibroblast, and epithelialization in wound healing of diabetic-rats.